2012
DOI: 10.1073/pnas.1203734109
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the human Cdc45/Mcm2-7/GINS helicase complex and its action with DNA polymerase ε in rolling circle DNA synthesis

Abstract: In eukaryotes, although the Mcm2-7 complex is a key component of the replicative DNA helicase, its association with Cdc45 and GINS (the CMG complex) is required for the activation of the DNA helicase. Here, we show that the CMG complex is localized to chromatin in human cells and describe the biochemical properties of the human CMG complex purified from baculovirus-infected Sf9 cells. The isolated complex binds to ssDNA regions in the presence of magnesium and ATP (or a nonhydrolyzable ATP analog), contains ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
155
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 26 publications
18
155
1
Order By: Relevance
“…The CMG complex is a highly processive and active helicase with high ATPase rates, whereas Mcm2-7 is a very poor ATPase, and particular reaction conditions are required to observe even weak activity in vitro (15)(16)(17). These data suggest that Cdc45 and GINS are required for full activation of the replication fork helicase (15,16).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The CMG complex is a highly processive and active helicase with high ATPase rates, whereas Mcm2-7 is a very poor ATPase, and particular reaction conditions are required to observe even weak activity in vitro (15)(16)(17). These data suggest that Cdc45 and GINS are required for full activation of the replication fork helicase (15,16).…”
mentioning
confidence: 80%
“…The CMG Complex May Be a Poor Helicase in Vitro because of the High Level of ssDNA Present in Biochemical Assays-Recent work by the Hurwitz group (17) demonstrates that the CMG helicase is processive only in the presence of a polymerase, RPA, or E. coli single-stranded binding protein. The data from this work suggest that the CMG complex may require E. coli SSB for processive helicase activity because singlestranded DNA present in these biochemical assays is toxic to the CMG.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the adaptation of yPold3 for Okazaki fragment processing and also by recent advances in the study of the GINS complex, which is a component of the eukaryotic initiation helicase, the CMG complex [MacNeill, 2010;Bermudez et al, 2011;Costa et al, 2011;Kang et al, 2012]. The recruitment of Pol a and Pol e to the GINS complex is a key step in initiation of DNA replication, and the association of Pol e with the GINS complex provides for a separate structural unit associated with ongoing leading strand synthesis [Seki et al, 2006;Chang et al, 2007].…”
Section: Role Of Pol D At the Replication Forkmentioning
confidence: 93%
“…6, lanes 3-6). Previous studies in HeLa cells showed that the hCMG complex was found stably associated only in the chromatin fraction (14). Histone H3, which is localized mostly on chromatin, was used as a quality control of the lysate fractionation (Fig.…”
Section: Significancementioning
confidence: 99%
“…The CMG complex, composed of stoichiometric levels of Cdc45, Mcm2-7, and GINS, was isolated from Drosophila embryos, as well as insect cells, using the baculovirus-expression system and found to contain 3′→5′ DNA helicase activity (12,13). Subsequently, the hCMG complex was purified and shown to support the coupled helicase-Pol e-dependent synthesis of leading strand DNA in vitro (14).…”
mentioning
confidence: 99%